The cryptic unstable transcripts are associated with developmentally regulated gene expression in blood-stage Plasmodium falciparum. Issue 6 (2nd June 2020) - Yin, Shigang; Fan, Yanting; He, Xiaohui; Wei, Guiying; Wen, Yuhao; Zhao, Yuemeng; Shi, Mingli; Wei, Jieqiong; Chen, Huiling; Han, Jiping; Jiang, Lubin; Zhang, Qingfeng
ABSTRACT: The tight gene expression regulation controls the development and pathogenesis of human malaria parasite Plasmodium falciparum throughout the complex life cycle. Recent studies have revealed the pervasive nascent transcripts in the genome of P. falciparum, suggesting the existence of a hidden transcriptome involved in the dynamic gene expression. However, the landscape and related biological functions of nascent non-coding RNAs (ns-ncRNAs) are still poorly explored. Here we profiled the transcription dynamics of nascent RNAs by rRNA-depleted and stranded RNA sequencing over the course of 48-h intraerythrocytic developmental cycle (IDC). We identified the genome-wide sources of a total of 2252 ns-ncRNAs, mostly originating from intergenic and untranslated regions of annotated genes. By integrating the nascent RNA abundances with ATAC-seq and ChIP-seq analysis, we uncovered the euchromatic microenvironment surrounding the ns-ncRNA loci, and revealed a positive correlation between ns-ncRNAs and corresponding mRNA abundances. Finally, by gene knock-down strategy, we showed that the cooperation of RNA exosome catalytic subunit PfDis3 and PfMtr4 cofactor played a major role in ns-ncRNAs degradation. Collectively, this study contributes to understanding of the potential roles of short-lived nascent ncRNAs in regulating gene expression in malaria parasites.